2019
DOI: 10.1007/s11661-019-05314-w
|View full text |Cite
|
Sign up to set email alerts
|

Role of Steel Plate Thickness on the Residual Stress Formation and Cracking Behavior During Flame Cutting

Abstract: Thick wear-resistant steel plates are utilized in challenging applications, which require a high hardness and toughness. However, utilization of the thick plates is problematic as they often have nonuniform mechanical properties along the thickness direction due to the manufacturing-induced segregations. In addition, the processing of thick plates commonly involves flame cutting, which causes several challenges. Flame cutting forms a heat-affected zone and generates high residual stresses during the cutting pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Thicker plates tend to have more segregations in the center region compared to thinner plates. In a previous study, [6] the segregation locations were found to have lower impact toughness and the fracture surfaces of the test samples showed more signs of brittle behavior compared to the surrounding regions.…”
Section: Introductionmentioning
confidence: 69%
See 4 more Smart Citations
“…Thicker plates tend to have more segregations in the center region compared to thinner plates. In a previous study, [6] the segregation locations were found to have lower impact toughness and the fracture surfaces of the test samples showed more signs of brittle behavior compared to the surrounding regions.…”
Section: Introductionmentioning
confidence: 69%
“…The lowest hardness occurs just after the two-phase region and then the hardness gradually increases as the tempering of the original structure decreases while going deeper toward the subsurface. [6,7] Both the hardness and the microstructure of the tempered region depend on the original microstructure of the steel plate. [6] In addition to microstructural changes and hardness variations, flame cutting causes high residual stresses in the cut edge of the steel plate.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations